Patients' Conceptualizations of Responsibility for Healthcare: A Typology for Understanding Differing Attributions in the Context of Patient Safety. (June 2019) - Heavey, Emily; Waring, Justin; De Brún, Aoife; Dawson, Pamela; Scott, Jason
This study examines how patients conceptualize "responsibility" for their healthcare and make sense of the complex boundaries between patient and professional roles. Focusing on the specific case of patient safety, narrative methods were used to analyze semistructured interviews with 28 people recently discharged from hospital in England. We present a typology of attribution, which demonstrates that patients' attributions of responsibility to staff and/or to patients are informed by two dimensions of responsibility: basis and contingency. The basis of responsibility is the reason for holding an individual or group responsible. The contingency of responsibility is the extent to which that attribution is contextually situated. The article contributes to knowledge about responsibility in complex organizational environments and offers a set of conceptual tools for exploring patients' understanding of responsibility in such contexts. There are implications for addressing patient engagement in care, within and beyond the field of patient safety.